Critical Review and Improvement of Bank Protection Methods in Nepalese Rivers - Kafle, Mukesh Raj (Journal of the Institute of Engineering, 2021)
This paper reviews performance of bank protection works constructed over the last decades along the major rivers in Nepal. The study reveals main reasons of early spurs failure in five major rivers - Koshi, Narayani, West Rapti, Karnali and Mahakali. The overview finds design deficiency as the main reason of failure of bank protection works. The methodology incorporates a combination of field visits and a review of design reports, master plans. The study finds bank protection works along the major rivers in Nepal consist almost exclusively of spurs often combined with revetments in between, made of gabions filled with boulders. Also, the launching aprons are constructed of gabions. The lifetime of these bank protection works is less than 10 years and often much shorter. Designs are based on standard designs from Indian standards, developed for normal alluvial rivers. The study recommends initiating a bank protection pilot project to identify the cause of failure of the bank protection works and to test remedial measures for the sustainability enhancement of river protection works in future.